Increased interdigitation zone visibility on optical coherence tomography following systemic fibroblast growth factor receptor 1‐3 tyrosine kinase inhibitor anticancer therapy. (26th May 2021) - Charng, Jason; Attia, Mary S.; Arunachalam, Sukanya; Lam, Wei‐Sen; Creaney, Jenette; Muruganandan, Sanjeevan; Read, Catherine; Millward, Michael; Spiro, Jon; Chakera, Aron; Lee, Y. C. Gary; Nowak, Anna K.; et al.
Abstract: Background: To describe ocular adverse events and retinal changes during fibroblast growth factor receptor (FGFR) inhibitor (AZD4547) anticancer therapy. Methods: This is a sub‐study examining ocular adverse effects from AZD4547 therapy (single‐centre, open‐label, single arm phase II clinical trial). Comprehensive ocular examinations were performed 3 weekly in 24 patients. Macular optical coherence tomography (OCT) scan (30 0  × 25 0 ) was obtained at each visit and OCT parameters [central 1 mm retinal thickness (CRT) and total macular volume in central 6 mm] extracted. OCT scans were subdivided into outer (ELM to RPE) and inner (ELM to ILM) layers to compare outer and inner retinal changes. Results: In 24 patients, AZD4547 was associated with eyelash elongation ( n  = 5, 21%) and punctate corneal erosion ( n  = 2, 8%). One patient developed clinically significant posterior capsular opacification during the study. OCT data were available in 23 patients, retinal changes ranged from an asymptomatic increased visibility of the interdigitation zone (IDZ) ( n  = 10, 43%) to multilobular subretinal fluid pockets ( n  = 5, 22%), which was associated with mild visual acuity loss. In a subset of patients ( n  = 9) with pre‐AZD4547 dosing OCT baseline, CRT increased by mean ( SD ) of 9 (4) μm in those with IDZ change only compared with 64 (38) μm in those with other retinal changes. Retinal changes tended to be bilateral, self‐limiting and improved over time without medical intervention. Conclusions: The ocular signs and symptoms did not result in dose cessation. Posteriorly, FGFR inhibition leads to outer retinal changes ranging from increased visibility of IDZ to distinct, multiple fluid pockets.